Intention to adopt XBRL-based digital reporting in Malaysia - Norazmi Ashari (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2010)
Standards for electronic recording, processing and dissemination of financial and other corporate reports (digital reporting) can provide benefits both for external regulation and investor relations and for internal financial management and decisionmaking. As far as available technologies for such purposes are concerned, XBRL is recognized as one of the best currently available today. Although this technology, which in itself is an innovation in the way financial information is stored and distributed, is actively being discussed and implemented at an international level, little effort is made towards its implementation in Malaysia. In light of this, one of the main objectives of this study is to examine a selected group of Malaysian listed companies' intention to adopt XBRL-based Digital Reporting (DR) systems. In addition, this study sets out to assess the capacity of the DoI theory's innovation attributes in measuring the Intention to Adopt in the context of a new innovation, which is XBRL in this case. Therefore, this study endeavors to evaluate which of the postulated innovation attributes are significantly influential in deciding the respondents' intention to adopt (or reject) the XBRL-based DR models proposed to them. This study uses the Three Levels of Digital Reporting Progress framework and the Diffusion of Innovation theory as the backbone mechanisms to find the solution for the research issues. Data were gathered by sending out questionnaires to selected companies listed on the main-board of Bursa Malaysia. The findings reveal that majority of the sample companies were still undecided over the plan of adopting XBRL-based DR systems. Moreover, there were more respondents who were skeptical about adopting the systems than those who felt positive about adopting them. The findings also reflect that the companies have already grasped the perceived effectiveness of the XBRLbased systems. However, they also made it clear that they were perturbed about the potential costs to be borne out of the systems' implementation. Furthermore, the findings from the correlation analyses confirmed the hypothesized positive relationships between a trio of Effectiveness, Compatibility and Trialability, and the intention to adopt. Meanwhile, despite being not significant, the assumed negative correlation was confirmed between the costs and the intention to adopt. Moreover, the results of linear regression analyses showed that trialability, compatibility and effectiveness of the models were significant, at various levels, in explaining the intention to adopt the innovations proposed.